PEREMPUAN YANG MENGUNDANG MAUT: ANALISA STRUKTUR NARATIF A. J. GREIMAS PADA FILM AIR TERJUN PENGANTIN - Kukuh Yudha Karnanta (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2015)
Abstract. This article discussed a movie entitled Air Terjun Pengantin, one of the horror movies played in Indonesia in 2010, by utilizing the theory of AJ Greimasâ€™s narrative structure to identify inherent discourse. The discussion aimed at dismantling the cinematic and narrative conventions so that the film could be received and understood. The analysis showed the existence of between men and women relationship as well as the image of women in the film. The relationship went so smooth under the patriarchal ideology internalized through some points and one of them was the film. Thus, both in form and content, Air Terjun Pengantin was one of the films that continues to vocalize patriarchal ideology and women stereotyping.Â Keyword: struktur naratif, aktansial, perempuan